Implikasi Promosi terhadap Nilai Pelanggan Produk Tabungan Anak IB Maslahah di Bank BJB Syariah KCP Padalarang - Maryanto, Maryanto; Ma’mun, Saepul; Maryati, Maryati; Solihin, Dadin (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2026)
This study aims to determine the influence of promotional tendencies on customer value in iB Maslahah Child Savings products at Bank BJB Syariah KCP Padalarang. Promotion is an important aspect in evaluating the company's performance and encouraging increased customer attraction through communication strategies carried out by the company's human resources. This study uses a quantitative approach with a population of 712 customers and a sample of 90 respondents obtained through purposive sampling techniques. Data collection was carried out by distributing questionnaires and analyzed using the SPSS program version 27.0. The results of the study showed that: (1) the results of a simple linear regression analysis showed that every 1% increase in promotions would increase customer value by 0.879 points, with a positive relationship direction; (2) the t-test results show a t-calculated value of 18.220 > t-table 0.2072, which means that H₀ is rejected and H₁ is accepted, or in other words, the promotion has a significant effect on the customer's value; (3) The promotion variable contributes 79% to customer value, while the remaining 21% is influenced by other variables that are not discussed in this study.